2014
DOI: 10.1016/j.jeem.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Does efficient irrigation technology lead to reduced groundwater extraction? Empirical evidence

Abstract: Policies that encourage the use of more efficiency irrigation technology are often viewed as effective, politically feasible methods to reduce the consumptive use of water for agricultural production. Despite their widespread use, these policies have not been subject to empirical evaluation. In this article, we evaluate the effect on groundwater extraction of a widespread conversion from traditional center pivot irrigation systems to higher efficiency dropped-nozzle center pivot systems that has occurred in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
215
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(223 citation statements)
references
References 38 publications
(32 reference statements)
6
215
0
2
Order By: Relevance
“…Some authors conclude either from simulation models that rebound effect exists but the magnitude is minor, below 3% such as Contor and Taylor (2013), Graveline et al (2013) or by empirical research as in Pfeiffer and Lin (2014), this small increase is justified by increased productivity or crop change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors conclude either from simulation models that rebound effect exists but the magnitude is minor, below 3% such as Contor and Taylor (2013), Graveline et al (2013) or by empirical research as in Pfeiffer and Lin (2014), this small increase is justified by increased productivity or crop change.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the observed increase may be explained by the evaporation of the drops travelling from the sprinklers to the ground (substitution of surface irrigation for sprinklers) and the irrigation of some plots inside the perimeter of the WUA that received scarce or no irrigation due to the deficiencies of the previous system (surface and open channels). Pfeiffer and Lin (2014) reported a small increase (1%-2%) in water depletion when traditional pivots were replaced by dropnozzle pivots. The reasons for the increase in evapotranspiration reported by these authors are unclear from the biophysical point of view and the authors recognized the need for additional research.…”
Section: Empirical Researchmentioning
confidence: 99%
“…This downward shift corresponded with a rise in water-efficient drop nozzle technology, substantially accelerated by state subsidies for irrigation upgrades. Prior research (50) found that the adoption of this technology actually increased water use, as increased irrigation efficiency reduced the cost of an effective unit of water, inducing farmers to irrigate a greater proportion of their acreage and plant more water-intensive crops. The downward shift of the price function reflects the fact that the technological shift actually made water appear less scarce, reducing the value of a greater water stock (or the apparent cost of depleting water today).…”
Section: Pðsþ =mentioning
confidence: 99%
“…Consequently, in many areas all these efforts have not been reflected so far in a reversal of the long-term trend of increasing water use. Quite the contrary, several irrigation networks worldwide have experienced an increase in water demand parallel to the modernization of irrigation infrastructures (Ding and Peterson, 2006;Gutierrez-Martin and Gomez, 2011;Pfeiffer and Lin, 2010).…”
Section: Discussionmentioning
confidence: 99%